16S rRNA Sequencing Detected Profftella, Liberibacter, Wolbachia, and Diplorickettsia from Relatives of the Asian Citrus Psyllid - Nakabachi, Atsushi; Malenovský, Igor; Gjonov, Ilia; Hirose, Yuu (Microbial ecology, 2020)
The Asian citrus psyllid Diaphorina citri (Hemiptera: Psylloidea) is a serious pest of citrus species worldwide because it transmits Candidatus Liberibacter spp. (Alphaproteobacteria: Rhizobiales), the causative agents of the incurable citrus disease, huanglongbing or greening disease. Diaphorina citri possesses a specialized organ called a bacteriome, which harbors vertically transmitted intracellular mutualists, Ca. Carsonella ruddii (Gammaproteobacteria: Oceanospirillales) and Ca. Profftella armatura (Gammaproteobacteria: Betaproteobacteriales). Whereas Carsonella is a typical nutritional symbiont, Profftella is an unprecedented type of toxin-producing defensive symbiont, unusually sharing organelle-like features with nutritional symbionts. Additionally, many D. citri strains are infected with Wolbachia, which manipulate reproduction in various arthropod hosts. In the present study, in an effort to obtain insights into the evolution of symbioses between Diaphorina and bacteria, microbiomes of psyllids closely related to D. citri were investigated. Bacterial populations of Diaphorina cf. continua and Diaphorina lycii were analyzed using Illumina sequencing of 16S rRNA gene amplicons and compared with data obtained from D. citri. The analysis revealed that all three Diaphorina spp. harbor Profftella as well as Carsonella lineages, implying that Profftella is widespread within the genus Diaphorina. Moreover, the analysis identified Ca. Liberibacter europaeus and Diplorickettsia sp. (Gammaproteobacteria: Diplorickettsiales) in D. cf. continua, and a total of four Wolbachia (Alphaproteobacteria: Rickettsiales) lineages in the three psyllid species. These results provide deeper insights into the interactions among insects, bacteria, and plants, which would eventually help to better manage horticulture.
Keywords: Symbiosis; RNA, Ribosomal, 16S; Sternorrhyncha; Hemiptera; Bacteria; RNA, Bacterial; mužské pohlaví; Microbiome; Wolbachia; Molecular phylogeny; bakteriální RNA; ženské pohlaví; RNA ribozomální 16S; Diaphorina; zvířata; symbióza; Bacterial endosymbiont; Francie; Insect; France; Female; Male; Animals